The Swedish Youth Labor Market in Boom and Depression - Per-Anders Edin; Anders Forslund; Bertil Holmlund (Uppsala University, Department of Economics, 1998)
This paper is concerned with the labor market experience of Swedish youths during the 1980s and the 1990s. The first objective is to portray early economic attainment among young Swedes. The second objective of the paper is to examine the impact of labor market programs on youth employment. We find that the slump in the 1990s has been associated with dramatic increases in youth unemployment and youth participation in active labor market programs. The impact on unemployment rates by age and education has been roughly proportional, however. The evolution of employment and unemployment does not offer much ground for the popular hypothesis that the recent rise in unemployment is driven by large and pervasive shifts in the demand for labor by skill attributable to technological innovation. The employment crisis has been met by an unprecedented increase in active labor market programs, in large part targeted at unemployed youths. There is a risk that these programs may crowd out regular youth employment, a hypothesis that is supported in our empirical investigation of regular youth employment in Swedish municipalities.
urn:nbn:se:uu:diva-2403
Keywords: E24; J21; J23; J31; J64; 330; Employment; Unemployment; Wages; Labour force and employment; Size and structure; Employment determination; Demand for labour